Petrogenesis of andesites in a Triassic volcanic arc in the southern South China Sea: constraints from whole-rock and mineral geochemistry - Wei, Wu; Liu, Chuan-Zhou; Yan, Wen; Zhong, Li-Feng (Frontiers in Earth Science, 2025)
Calc-alkaline andesitic rocks are prominently exposed as a major product of subduction-related magmatism. The identification of Late Triassic andesites in Meiji Atoll, located in the southern South China Sea (SCS), provides new insights into the regional magmatic evolution and geodynamic setting of the southern SCS margin during the early Mesozoic era. Here, we present structured illumination microscopy (SIMS) U-Pb zircon ages, zircon Hf-O isotopic compositions, whole-rock and mineral geochemistry, as well as Sr-Nd-Hf-Pb isotopic compositions of andesites drilled in the Meiji Atoll. Geochronological results indicate that the crystallization ages of the andesites range from approximately 217 Ma to 225 Ma, which coincide with the eruption of interbedded dacites. The Meiji calc-alkaline andesites are characterized by a strong fractionation between light rare earth elements (LREEs) and heavy rare earth elements (HREEs), an enrichment of large ion lithophile elements (LILEs) such as Rb, K, U, and Pb, and a depletion of high-field strength elements (HFSEs), particularly Nb, Ta, and Ti, when compared to normal mid-ocean ridge basalts (N-MORB). These characteristics align with the typical geochemical signature of average continental arc andesites. The andesites display relatively high initial 87Sr/86Sr ratios (0.7083–0.7113), slightly enriched εNd(t) values (−6.07 to −4.9) and εHf(t) values (−7.70 to −2.16), along with variable zircon εHf(t) and δ18O values ranging from −2.93 to −1.99‰ and 4.0‰–9.0‰, respectively. The geochemical features of the andesites and zircons suggest they likely originated from a phlogopite-bearing metasomatized lithospheric mantle that had been influenced by subduction sediment compositions. Additionally, the geochemical characteristics and thermobarometry results of amphibole phenocrysts imply continuous and cryptic amphibole fractionation during the evolution of the arc magma. U-Pb ages and Hf isotopic data from the zircon xenocrysts exhibit a similar pattern to those from the eastern South China Block, providing compelling evidence for the existence of a Paleoproterozoic crystalline basement beneath the Nansha Block, akin to the Cathaysia Block. The identified volcanism at Meiji Atoll likely reflects the spatial variation in the distribution of arc magmatism along the South China Block. It might also represent the earliest re-initiation of continental arc magmatism following a phase of flat-slab subduction of the paleo-Pacific.